1998
DOI: 10.1055/s-0037-1614211
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Subsequent Malignancy in Patients Presenting with Deep Vein Thrombosis: Results from a Historical Cohort Study

Abstract: SummaryBackground: Several studies have reported that patients who present with idiopathic deep vein thrombosis (DVT) have an increased risk of subsequently developing cancer. A clinical trial had previously been conducted examining the optimal duration of oral anticoagulant therapy following initial heparin treatment in patients with proximal DVT.Methods: A historical cohort study was performed on patients enrolled in the duration of anticoagulant trial. Patients known to have cancer at the time of entry into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 12 publications
4
29
2
Order By: Relevance
“…44 On the basis of results from cohort studies and clinical trials, Ϸ10% of persons presenting with idiopathic VTE are subsequently diagnosed with cancer over 5 to 10 years, and the diagnosis is established within the first year of presentation of DVT in Ͼ75% of cases. 5,[42][43][44][45][46][47] This likelihood of identifying occult cancer after an episode of idiopathic VTE is supported by 2 population registry studies. Using data from national hospital and cancer registries, Baron et al found that the standardized incidence ratio (SIR, the observed number of cases divided by the expected number of cases in the age-matched normal population) was 4.4 for cancer at 1 year after diagnosis of VTE.…”
Section: The Association Between Vte and Occult Cancermentioning
confidence: 89%
See 1 more Smart Citation
“…44 On the basis of results from cohort studies and clinical trials, Ϸ10% of persons presenting with idiopathic VTE are subsequently diagnosed with cancer over 5 to 10 years, and the diagnosis is established within the first year of presentation of DVT in Ͼ75% of cases. 5,[42][43][44][45][46][47] This likelihood of identifying occult cancer after an episode of idiopathic VTE is supported by 2 population registry studies. Using data from national hospital and cancer registries, Baron et al found that the standardized incidence ratio (SIR, the observed number of cases divided by the expected number of cases in the age-matched normal population) was 4.4 for cancer at 1 year after diagnosis of VTE.…”
Section: The Association Between Vte and Occult Cancermentioning
confidence: 89%
“…4 Similarly, there is a higher incidence of subsequent cancer in patients with idiopathic thrombosis than in those with a definite but transient risk factor at the time of VTE (Table 1). 5,[42][43][44][45][46] The variation in reported incidence likely reflects the different definitions for idiopathic and secondary cases, and variation in the intensity of cancer surveillance in each study. In a pooled analysis of these studies, the odds ratio for subsequent cancer in patients presenting with idiopathic VTE compared with secondary VTE was 4.8.…”
Section: The Association Between Vte and Occult Cancermentioning
confidence: 99%
“…While the first author found a significant increased risk for cancer in subjects with VTE versus those without (4.8% versus 1.5%, P < 0.0001) the latter did not (2.5 versus 2.7, P = 0.20). In all but one of the four large retrospective studies published between 1997 and 1998 and collecting more than 1500 patients [75][76][77][78], the incidence of cancer in patients with presumed idiopathic VTE was significantly higher (two-to threefold) than in patients with secondary VTE. In the retrospective studies by Sorensen and colleagues [79] and Baron and colleagues [80] the incidence of cancer was increased during the first year following the diagnosis of VTE and the effect persisted for up to 10 years.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…All these mechanisms lead to the activation of coagulation factor X and the clotting cascade. In a study of patients with idiopathic thrombosis, almost 10% were diagnosed with cancer in 5–10 subsequent years [9]. …”
Section: Association Of Venous Thromboembolism With Cancermentioning
confidence: 99%